Application of growth monitoring charts by health care providers in Village Health and Nutrition Day (VHND) setting in rural Kamrup - Barua, Kabita; Baruah, Rupali (Indian Journal of Community Health, 2014)
Background: Growth monitoring attempts to promote optimal growth through effective education to caregivers; detection of ‘early growth faltering’, ‘underweight’ and initiation of relevant action. Objectives: (i) To observe application of the growth monitoring charts provided in the Mother and Child Protection (MCP) Card by health care providers in Village Health and Nutrition Day (VHND) setting in rural Kamrup. (ii) To assess whether their applied methods and interpretations are appropriate. (iii) To identify gaps in relation to growth monitoring. Materials and Methods: A cross-sectional study was conducted during January-July 2014 in VHND sessions covering 44 villages selected through multistage sampling in Kamrup district in Assam. 88 Auxiliary Nurses and Midwives (ANM) and 34 Anganwadi Workers (AWW) present in the sessions were closely observed during their activities and then interviewed regarding their interpretations of the growth chart. Results: 77% of the AWWs present were involved in growth assessment and weight plotting in growth charts of all the 0-36 months aged children brought to a session. Correct plotting of weight and interpretations of the growth charts were known to 94% of the AWWs and only 69% of the ANMs. Conclusion: Growth monitoring charts provided in the MCP card were not found to be optimally applied for community based growth monitoring in rural Kamrup. Deficiency was found in the ANMs regarding their applied methods and interpretations of the growth charts in comparison to the AWWs. AWWs were inadequately involved in growth assessment and monitoring of children in the vulnerable age group of 0-36 months in the VHND sessions.